Soviet studies on Turkey, 1917-1991: institutional history and analytical perspectives - Şahin, Liaisan. (Thesis (M.A.)-Bogazici University. Atatürk Institute for Modern Turkish History, 2005., 2005)
Turkish studies represent one of the oldest and most developed branches of Russian Orientalstudies. The peculiarities of Russian-Turkish relations and Russia̕s consequent close interest inTurkey have determined the fact. In the Soviet period, Turkish studies continued to develop and showed steady proliferation and advance, because Turkey served for Soviet Orientalist scholarshipas a model in elaborating many of the problems of the Third World. It stemmed from somepeculiarities of Turkish development, namely, the fact that Turkey won its political independentmuch earlier of the majority of colonial and semi-colonial countries and had a long experience in capitalist way of socioeconomic development. This thesis attempts a comprehensive history ofSoviet studies on Turkey, considering them within the context of the overall development of SovietOriental studies. Along with institutional history, some aspects of the Soviet analysis of Turkey aredealt with: the Soviet interpretation of the two most important Soviet Turkologist scholarship themes, the Turkish National Struggle and socioeconomic development of the Republic of Turkey, is conveyed. It is indicated that Soviet studies on Turkey showed an obvious continuity with the Tsarist Turkology in regard to the priorities of investigation, as the same focus on contemporaryissues and the primary engagement with recent history and economics were the case. Soviet Turkology developed parallel to the overall growth of Soviet Oriental studies and wascharacterized by a quick response to the state̕s demands and to the major trends of research. As tothe peculiarities of the Soviet analysis, the Turkish National Struggle was considered by Sovietscholars as a bourgeois liberation revolution under the leadership of the native merchant bourgeoisie and big land-owners and its anti-people character was emphasized. The Sovietscholarship was of the opinion that capitalism in Turkey was characterized by the middle level ofdevelopment; the strong state element; the existence of many feudal remnants and consequentcontradictions and disproportions in socioeconomic structure; and unequal dependence on the world capitalist system.